“Coming here you should speak English”: performing creativity on a YouTube channel for teaching speaking - Nurul Amalia Setyaningsih; Irra Wahidiyati (English Language Education Study Program, Faculty of Education and Teacher Training, Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, Indonesia, 2022)
The present study aims to explore strategies in teaching speaking using YouTube as media as well as the advantages and disadvantages of this platform in teaching speaking. Nested in a narrative case study approach, data were garnered through interviews using WhatsApp and Google Forms. An EFL teacher who is also a YouTuber and six students in tenth grade of a senior high school in Purwokerto, Central Java, Indonesia volunteered to participate. Study findings demonstrate that the EFL teacher integrated technology, i.e., YouTube, as a learning medium, and she provided video learning videos according to the material needed by students. The teacher designed a learning video with herself as a role model. Before uploading it on YouTube, the teacher watched the video first and edited some errors. The study also reveals several advantages of using YouTube in teaching speaking. YouTube videos promoted the teacher’s creativity in employing technology as learning media. Students could learn anywhere and anytime through videos on YouTube and practiced from videos of native speakers. Conversely, adopting YouTube videos in a speaking class had disadvantages, such as the selection of YouTube videos relevant to learning materials, restricted opportunities to have feedback from their teachers, and poor internet connection.